Targeted delivery of antibiotics to the infected pulmonary tissues using ROS-responsive nanoparticles - Yu Wang (Journal of Nanobiotechnology, 2019)
Abstract Background Immunocompromised individuals and those with lung dysfunction readily acquire pulmonary bacterial infections, which may cause serious diseases and carry a heavy economic burden. Maintaining adequate antibiotic concentrations in the infected tissues is necessary to eradicate resident bacteria. To specifically deliver therapeutics to the infected pulmonary tissues and enable controlled release of payloads at the infection site, a ROS-responsive material, i.e. 4-(hydroxymethyl) phenylboronic acid pinacol ester-modified α-cyclodextrin (Oxi-αCD), was employed to encapsulate moxifloxacin (MXF), generating ROS-responsive MXF-containing nanoparticles (MXF/Oxi-αCD NPs). Results MXF/Oxi-αCD NPs were coated with DSPE-PEG and DSPE-PEG-folic acid, facilitating penetration of the sputum secreted by the infected lung and enabling the active targeting of macrophages in the inflammatory tissues. In vitro drug release experiments indicated that MXF release from Oxi-αCD NPs was accelerated in the presence of 0.5 mM H2O2. In vitro assay with Pseudomonas aeruginosa demonstrated that MXF/Oxi-αCD NPs exhibited higher antibacterial activity than MXF. In vitro cellular study also indicated that folic acid-modified MXF/Oxi-αCD NPs could be effectively internalized by bacteria-infected macrophages, thereby significantly eradicating resident bacteria in macrophages compared to non-targeted MXF/Oxi-αCD NPs. In a mouse model of pulmonary P. aeruginosa infection, folic acid-modified MXF/Oxi-αCD NPs showed better antibacterial efficacy than MXF and non-targeted MXF/Oxi-αCD NPs. Meanwhile, the survival time of mice was prolonged by treatment with targeting MXF/Oxi-αCD NPs. Conclusions Our work provides a strategy to overcome the mucus barrier, control drug release, and improve the targeting capability of NPs for the treatment of pulmonary bacterial infections.